2023
DOI: 10.1002/fft2.231
|View full text |Cite
|
Sign up to set email alerts
|

Huangjing—From medicine to healthy food and diet

Abstract: Diet‐related chronic diseases are becoming more common where many consumers and nutritionists are seeking food and lifestyle interventions to improve health and standard of living. To supplement regular dietary intake, scientists are seeking to develop new crops that are productive and nutritious, which can improve health outcomes. This review focused on the history of Huangjing as a medicine, healthy food as part of a diverse diet and as an input into pharmacology uses. The sustainable production of Huangjing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 138 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…While Huangjing has been reported to bring considerable benefits to farmers, with yields of 1500 kg of dried product per hectare after four years of cultivation [25] and a price after processing of USD 55.6/kg, roughly five times the cost of the raw materials (USD 10.43/kg) [3], people have begun to artificially plant P. cyrtonema to increase income. Jiao et al [26] reported all new Polygonatum Mill.…”
Section: Introductionmentioning
confidence: 99%
“…While Huangjing has been reported to bring considerable benefits to farmers, with yields of 1500 kg of dried product per hectare after four years of cultivation [25] and a price after processing of USD 55.6/kg, roughly five times the cost of the raw materials (USD 10.43/kg) [3], people have begun to artificially plant P. cyrtonema to increase income. Jiao et al [26] reported all new Polygonatum Mill.…”
Section: Introductionmentioning
confidence: 99%
“…The rhizome of Polygonatum has been eaten in China for over 2000 years as a food and as a medicine [22]. It exhibits enormous market potential with more than 150 proprietary Chinese medicines and more than 350 health foods among the developments of its raw materials.…”
Section: Introductionmentioning
confidence: 99%